Semantics in Acquisition - van Geenhoven, Veerle (Studies in Theoretical Psycholinguistics, 2006)
This book is unique in that it relates two linguistic subfields: Semantics and Language Acquisition. The volume contains a collection of writings that focuses on semantic phenomena and their interpretation in the analysis of the language of a learner. The variety of phenomena that are addressed is substantial: temporal aspect and tense, specificity, quantification, scope, finiteness, focus structure, and focus particles. The number of languages in which these phenomena are investigated is very large as well: Dutch, English, German, Inuktitut, Italian, Japanese, and Polish, to name a few. The volume creates a theoretical as well as an empirical bridge between semantic research on the one hand and psycholinguistic acquisition studies on the other.